LncRNA NEAT1 Knockdown Inhibits Retinoblastoma Progression by miR-3619-5p/LASP1 Axis - Chen, Xuedong; Zhao, Shiyong; Li, Qingjun; Xu, Caicai; Yu, Yongbin; Ge, Hongyan (Frontiers in Genetics, 2020)
Retinoblastoma (RB) is the most common intraocular tumor in childhood. Long non-coding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 (NTAT1) has been reported to be related to RB progression. This study aims to study the molecular mechanism of NEAT1 in regulating cell cycle, proliferation, apoptosis, migration and invasion in RB. The expression levels of NEAT1 and miR-3619-5p were detected by quantitative real time polymerase chain reaction (qRT-PCR). The protein expression of LIM and SH3 domain protein 1 (LASP1) was measured by western blot. The proliferation of RB cells was analyzed by cell counting kit-8 (CCK-8) and cell colony formation assays. Cell migration and invasion were evaluated by transwell assay. Cell cycle and apoptosis were assessed by flow cytometry analysis. The association between miR-3619-5p and NEAT1 or LASP1 was predicted by starBase 3.0 database, and identified by dual-luciferase reporter assay. The effects of NEAT1 knockdown on the tumor growth in vivo were detected by in vivo tumor formation assay. NEAT1 expression was dramatically up-regulated and miR-3619-5p expression was obviously down-regulated in RB tissues and cells compared with control groups. The protein level of LASP1 was obviously increased in RB tissues or cells relative to paracancerous normal tissues or cells, respectively. Functionally, NEAT1 silencing inhibited RB cell migration, invasion and proliferation, whereas induced cell apoptosis and cell cycle arrest in RB, whereas this phenomenon was partially abolished by miR-3619-5p inhibitor. Mechanistically, NEAT1 acted as a sponge of miR-3619-5p and miR-3619-5p was associated with LASP1. In addition, NEAT1 knockdown decreased the volume and weight of RB tumor in vivo. Together, NEAT1 silencing repressed cell migration, invasion and proliferation, whereas induced cell apoptosis and cycle arrest by sponging miR-3619-5p to inhibit LASP1 expression in RB cells. This study may provide a theoretical basis for RB therapy.